Influence of race distance and biological sex on age-related declines in triathlon performance: Part B - Wu, S. S. X. (Journal of Science and Cycling, 2013)
The aim of this study was to investigate the influence of biological sex and age on the pacing strategies adopted by non-drafting top triathletes during the cycle and run disciplines of a Sprint, Olympic, half-Ironman and Ironman triathlon. Split times of the top 20% non-elite males (n=468) and females (n=146) were determined using official race transponders and a video capture system for pre-determined sections of the cycle and run disciplines of four triathlon distances. Indices of pacing were calculated to compare between sexes and age-groups. Results of this study indicated that different pacing strategies were adopted between athletes of different age and sex over the various triathlon disciplines and distances. Females were more aggressive during the initial stages of the cycling discipline across all distances (sprint - 2.1% p=0.024; Olympic - 1.6%, p=0.011; half-Ironman- 1.5%, p<0.001; Ironman - 1.7%, p<0.001 higher relative to mean) compare with males. Younger athletes (20-29 y) tend to begin the run faster (2.0 to 3.0% faster than other age-groups, p<0.029) during the sprint, Olympic and half-Ironman triathlons. These results indicate that different pacing strategies are adopted by non-drafting top athletes of different age and sex. Optimal pacing strategies may differ between sex and ages; therefore individuals may need to trial different strategies to develop their own optimal pacing profile for triathlon events of varying distances.